Sociobiology and evolutionary psychology - Rolston, Holmes, 1932-2025, author; Macmillan Reference USA, Thomson-Gale, publisher (Colorado State University. Libraries, 2005)
Sociobiology and evolutionary psychology are related fields both of which claim that biology is the principal determinant in human affairs. A frequent motif is that the basic thrust of all life is "selfish." Critics claim that there is, even in biology, more than one way of framing this behavior. Further, this fails to recognize the novel dimensions emergent with human culture. Persons with essentially the same genetic makeup can be converted from one worldview to another. Humans often operate with more inclusive religious and moral convictions that have little to do with selfish genes.
Keywords: human affairs; biology; religion; cultural development; genes; Darwinism